The Digital Interpreter: What is Natural Language Processing in Healthcare? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Natural Language Processing NLP, a core component of artificial intelligence AI, is rapidly transforming the healthcare landscape. It is the technology that ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care